2004
DOI: 10.1093/treephys/24.12.1333
|View full text |Cite
|
Sign up to set email alerts
|

Root distribution ofPinus pinaster,P. radiata,Eucalyptus globulusandE. kochiiand associated soil chemistry in agricultural land adjacent to tree lines

Abstract: We quantified the extent and distribution of roots of four commonly planted tree species (Eucalyptus globulus Labill., Pinus radiata D. Don, P. pinaster Aiton and E. kochii Maiden & Blakely subsp. plenissima C.A. Gardner) in agricultural land adjacent to tree lines, and examined the effect of soil type and root pruning on root morphology. Root distribution in soil adjacent to tree lines was mapped by a trench profile method at 13 sites on the south coast of Western Australia. Soil samples were collected to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
37
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 0 publications
7
37
1
Order By: Relevance
“…This could probably (Carberry et al, 2007;Hou et al, 2003) and for eucalypts, the common range was observed be attributed to the distance to which the shade extends to. The edge effect distance from tree-crop interface differ between species and sites to be 12 m in Ethiopian highlands (Kidanu et al, 2005) and up to 44 m in Australia (Sudmeyer et al, 2004). The crop field area prone to woodlot tree suppression observed in this study (zone A) is slightly lower than this range.…”
Section: Discussionmentioning
confidence: 53%
“…This could probably (Carberry et al, 2007;Hou et al, 2003) and for eucalypts, the common range was observed be attributed to the distance to which the shade extends to. The edge effect distance from tree-crop interface differ between species and sites to be 12 m in Ethiopian highlands (Kidanu et al, 2005) and up to 44 m in Australia (Sudmeyer et al, 2004). The crop field area prone to woodlot tree suppression observed in this study (zone A) is slightly lower than this range.…”
Section: Discussionmentioning
confidence: 53%
“…However, for logistical reasons we could only register the trees within 15 m around the core-sampling points. The maximum radial extent of trees is likely to vary depending on environmental conditions and size of trees but generally ranges from 1.5 to 4 times tree height [22]. In absolute distance terms, eucalypts from semi-arid environments show considerable radial root growth (e.g., ca.…”
Section: Discussionmentioning
confidence: 99%
“…In absolute distance terms, eucalypts from semi-arid environments show considerable radial root growth (e.g., ca. 20 m for E. camaldulensis [26], up to 39 m in E. globulus [22], in excess of 15-16 m for E. leucoxylon and E. trivalva (cited in Stone and Kalisz [21]). The fact that our modelling and inventory of vegetation around each core were limited to 15 m, could underestimate the potential contribution of plants that are located beyond these distances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other root functions such as synthesis and storage are considered secondary. Anchorage depends largely on proprieties of the root nearest the stem base and is most significant as a root function install plants, notably trees (Fitter, 1999;Sudmeyer et al, 2004). The ability to acquire resources from soil is a fundamental requirement for all plants, and is determined by four features of root systems: their architecture, their interactions with microorganisms, their ability to influence the rhizosphere by exudation, and their systems for transporting material across membranes.…”
Section: State Of the Art And Future Objectivesmentioning
confidence: 99%